2004
DOI: 10.1177/0042085904263063
|View full text |Cite
|
Sign up to set email alerts
|

Improving Race Relations in Higher Education

Abstract: This article suggests that colleges and universities can improve intergroup relations on campus by implementing a cooperative learning technique known as the jigsaw classroom. What is argued is that use of the jigsaw classroom will facilitate a recategorization process by which members of racial-ethnic groups other than one's own ("them") will begin to be seen as being members of a more inclusive "we." Included in this article is an examination of on-campus racial discrimination, a discussion of some social ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Similar conclusions can be reached when focusing on the inclusive effects of socioemotional learning programs, which primarily target the quality of relationships between students but can also impact factors of classroom climate associated with instruction (Durlak et al, 2011;Sklad et al, 2012). Moreover, hypothetical elements of IMT (e.g., Jigsaw cooperative method), often initially suggest fostering one factor of inclusive classroom climate (e.g., improving intergroup attitudes, Williams, 2004). But they may also undermine another factor (e.g., engagement, Cochon Drouet et al, 2022).…”
Section: A Multilevel Multi-factor Classroom Climate Measure To Bette...mentioning
confidence: 61%
“…Similar conclusions can be reached when focusing on the inclusive effects of socioemotional learning programs, which primarily target the quality of relationships between students but can also impact factors of classroom climate associated with instruction (Durlak et al, 2011;Sklad et al, 2012). Moreover, hypothetical elements of IMT (e.g., Jigsaw cooperative method), often initially suggest fostering one factor of inclusive classroom climate (e.g., improving intergroup attitudes, Williams, 2004). But they may also undermine another factor (e.g., engagement, Cochon Drouet et al, 2022).…”
Section: A Multilevel Multi-factor Classroom Climate Measure To Bette...mentioning
confidence: 61%
“…One all-time favorite collaborative technique that strengthens relations among diverse groups (Williams, 2004) and promotes deeper community in the classroom is the jigsaw. In this 2-stage activity, illustrated in Figure 1, students first work in "expert" groups and later form "jigsaw" groups.…”
Section: Jigswmentioning
confidence: 99%
“…Since everyone must share their expert group's content, success depends on no one member of the jigsaw group dominating the discussion. Through these "positive, non-superficial interactions with others" (Williams, 2004), students recategorize classmates from other backgrounds into their in-group, improving their view not only of the individual classmate but of that classmate's racial-ethnic group altogether. The techniques discussed in this review-the hall of fame, alternative discussion boards, and jigsaws-are 3 class activities that can be used to foster community, belonging, and persistence throughout a course in any discipline or modality.…”
Section: Stage 2: Jigsaw Groupsmentioning
confidence: 99%
“…Originally developed by Aronson et al (1978), the Jigsaw method aims to reduce intergroup prejudices in schools (Williams, 2004). After making some observations, Aronson et al (1978) concluded that intergroup aggressiveness was due to the competitive classroom environment.…”
Section: Introductionmentioning
confidence: 99%